Konsep Kebahagiaan Menurut Hadis Nabi dan Relevansinya dengan QS An-Nahl : 97 - Syifaullah, Syifaullah (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2025)
Happiness is a state of mind or feeling of pleasure and peace in life, both physically and spiritually, which serves to enhance self-vision. In Islam, happiness is not only about worldly matters but also about life after death. As the Messenger of Allah and the narrator of hadiths, Prophet Muhammad (peace be upon him) provides profound insights into how humans can achieve true and eternal happiness. His hadiths not only serve as a source of law and practical guidance for the daily lives of Muslims but also as moral and spiritual guidance touching on various aspects of life, enabling a Muslim to attain happiness in both this world and the hereafter. This study aims to identify and understand the factors that influence happiness based on hadiths. The discussion explores the concept of happiness, its causes, and how to achieve it. The method used in this study is a contemporary thematic analysis of hadiths. The study concludes that it is essential for individuals to know and understand everything that leads to happiness.